Widening access in a fee-deregulated system: exploring contemporary ideals of 'fair' access to higher education - Pitman, Tim (Open University, 2015)
This article explores the notion of 'fairness' in higher education policy, analysing the proposed 2014 reforms of the Australian higher education sector and with particular reference to the attempt to deregulate student tuition fees and introduce a national, equity scholarships scheme. Contemporary theorisations of fairness in higher education focus on discourses of merit, access and participation and widening participation through policies of distributive justice. However, a critical analysis of key policies, statements and public submissions concerning the above-mentioned reforms revealed a much stronger discourse of finding an accord between public and private funding of higher education and the corresponding public and private benefits. This understanding of fairness to some extent synthesises key neo-liberal and emancipatory themes. Under a 'shared-burden' approach to higher education costs, increases to student tuition fees are not necessarily opposed by the wider public. However in this instance, a failure to quantify the recalibrated costs proved fatal to the policy reforms. Moreover, this understanding of fairness as a shared burden between the state and the individual is one which needs to better-clarify the distinction between policies designed to increase access to higher education and those calculated to widen it.